Guest Editorial - Kumar, Anuj; Naim, Arshi; Kaur Nagra, Gagandeep; Kumar, Arya (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This special focus issue belongs to the annual conference on “Innovating for Impact: Digital Technologies for Public Administration, Engineering Application, Environmental Protection, Sustainable Business Operations, and Healthcare.” This conference was organized by Confab 360 Degree in collaboration with Manipal Academy of Higher Education, Dubai Campus; Rushford Business School, Switzerland; and European Global Institute of Innovation and Technology, Malta, on 19th and 20th February 2025. The official venue of the conference was the Manipal Academy of Higher Education, Dubai Campus. The chief patron(s) of the conference were Prof. (Dr.) S. Sudhindra, MAHE, Dubai; Prof. (Dr.) Tufail Syed; Prof. (Dr.) Padmakali Banerjee; and Prof. (Dr.) Nishu Ayedee. The patron(s) of the conference were Prof. (Dr.) Anuj Kumar, Prof. (Dr.) S.K. Pandey, Prof. (Dr.) Sunitha Prabhuram, Prof. (Dr.) Alok Satsangi, and Prof. (Dr.) Kanika Gupta. Prof. (Dr.) Anuj Kumar was also heading the editorial board of the conference. In this conference, more than 400 papers have been received, and 160 papers have been shortlisted for the conference presentation. More than 400 authors have participated in the conference as authors and co-authors of the papers. Out of 160 papers, 10 extended papers have been shortlisted for the special issue of the International Journal of Interactive Mobile Technologies. The authors have reviewed and revised these papers before shortlisting them.